The suggestive technologies as a condition of vocational training of the teacher of music - V.M. Semenjak (Academy of Cognitive and Natural Sciences, 2007)
In article application the suggestive technologies which promote successful mastering of the realized and not realized components of mentality during mastering a material is considered. Use auto-trainings, various kihtl.s of meditations for development of emotional - shaped sphere is offered.